2014
DOI: 10.1055/s-0034-1375684
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*1502 Increases the Risk of Phenytoin or Lamotrigine Induced Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis: Evidence from a Meta-analysis of Nine Case-control Studies

Abstract: There is a significant association between HLA-B*1502 and PHT or LTG-induced SJS/TEN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…HLA B*15:02 is associated with SJS and TEN due to CBZ intake in Han Chinese population, but not with MPE 6. Evidence from another meta-analysis of nine case-control studies by Li X et al shows significant association between HLA-A*15:02 and PHT and LTG-induced SJS/TEN 19. A pilot-study showed that the same allele may be associated with OXC-induced mild cutaneous reactions 20.…”
Section: Discussionmentioning
confidence: 99%
“…HLA B*15:02 is associated with SJS and TEN due to CBZ intake in Han Chinese population, but not with MPE 6. Evidence from another meta-analysis of nine case-control studies by Li X et al shows significant association between HLA-A*15:02 and PHT and LTG-induced SJS/TEN 19. A pilot-study showed that the same allele may be associated with OXC-induced mild cutaneous reactions 20.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding could be replicated only in Han Chinese subjects receiving carbamazepine; in Japanese and Korean subjects receiving carbamazepine, different HLA-B families are found to be related to SJS 15,16. At the present time, most published reports are focused on the relationship between HLA-B families and antiepileptic drugs only 17,18. Although some reports suggest that genetic screening techniques should be devised to screen for the risk of SJS before prescribing such drugs for patients with either epilepsy19,20 or mood disorder,21 another report has tried to investigate the implication of this pharmacogenetics technique in terms of other drugs, but this seems not implacable to be promoted to other drugs at the present time 22…”
Section: Resultsmentioning
confidence: 92%
“…Certain medications such as phenytoin, carbamazepine, and lamotrigine may cause Stevens-Johnson syndrome or toxic epidermal necrolysis. 50,51 Although rare, if one of those disorders is ignored and the medication continues to be administered, either Stevens-Johnson syndrome or toxic epidermal necrolysis can evolve into a life-threatening situation.…”
Section: Dermatologicmentioning
confidence: 99%